2017
DOI: 10.1128/mcb.00470-16
|View full text |Cite
|
Sign up to set email alerts
|

FBXL5 Inactivation in Mouse Brain Induces Aberrant Proliferation of Neural Stem Progenitor Cells

Abstract: FBXL5 is the substrate recognition subunit of an SCF-type ubiquitin ligase that serves as a master regulator of iron metabolism in mammalian cells. We previously showed that mice with systemic deficiency of FBXL5 fail to sense intracellular iron levels and die in utero at embryonic day 8.5 (E8.5) as a result of iron overload and subsequent oxidative stress. This early embryonic mortality has thus impeded study of the role of FBXL5 in brain development. We have now generated mice lacking FBXL5 specifically in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…The oxidation of PTEN and activation of PI3K-AKT signaling in Fbxl5-KO mice indicates that ROS-mediated inhibition of PTEN causes mTORC1 activation (Yamauchi et al, 2017). Moreover, this study also reported that the chemical inhibition of AKT and mTORC1 is sufficient to promote NSC differentiation in vitro and in vivo (Yamauchi et al, 2017). The functions of mTORC1 activity in aging NSC populations have also been investigated.…”
Section: Mtor Signaling In Stem and Progenitor Cellsmentioning
confidence: 65%
See 2 more Smart Citations
“…The oxidation of PTEN and activation of PI3K-AKT signaling in Fbxl5-KO mice indicates that ROS-mediated inhibition of PTEN causes mTORC1 activation (Yamauchi et al, 2017). Moreover, this study also reported that the chemical inhibition of AKT and mTORC1 is sufficient to promote NSC differentiation in vitro and in vivo (Yamauchi et al, 2017). The functions of mTORC1 activity in aging NSC populations have also been investigated.…”
Section: Mtor Signaling In Stem and Progenitor Cellsmentioning
confidence: 65%
“…A number of other factors also appear to regulate mTOR activity in NSCs and during neural development and ageing. The NSCspecific deletion of F box and leucine-rich repeat protein 5 (Fbxl5), for example, increases mTORC1 activation and impairs NSC differentiation and brain development (Yamauchi et al, 2017) (Fig. 4A).…”
Section: Mtor Signaling In Stem and Progenitor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…F‐box proteins constitute a large family of >70 eukaryotic proteins (Jin et al, ), but the substrates of each F‐box protein have remained largely unknown. To identify substrates for a given F‐box protein, we previously developed a method termed differential proteomics‐based identification of ubiquitylation substrates (DiPIUS; Yumimoto, Matsumoto, Oyamada, Moroishi, & Nakayama, ), and we have applied this method to several systems (Nakajima et al, ; Nakayama, Yumimoto, Kawamura, & Nakayama, ; Nishiyama, Nita, Yumimoto, & Nakayama, ; Watanabe, Yumimoto, & Nakayama, ; Yamauchi, Nishiyama, Moroishi, Kawamura, & Nakayama, ; Yumimoto, Matsumoto, Onoyama, Imaizumi, & Nakayama, ).…”
Section: Introductionmentioning
confidence: 99%
“…Genes to Cells SUGIYAMA et Al. (Nakajima et al, 2015;Nakayama, Yumimoto, Kawamura, & Nakayama, 2018;Nishiyama, Nita, Yumimoto, & Nakayama, 2015;Watanabe, Yumimoto, & Nakayama, 2015;Yamauchi, Nishiyama, Moroishi, Kawamura, & Nakayama, 2017;Yumimoto, Matsumoto, Onoyama, Imaizumi, & Nakayama, 2013).…”
Section: Introductionmentioning
confidence: 99%